Comparison of Inflammation-Based Prognostic Scores in a Cohort of Patients with Resectable Esophageal Cancer. (27th June 2017) - Jomrich, G.; Paireder, M.; Gleiss, A.; Kristo, I.; Harpain, L.; Schoppmann, S. F.
Abstract : Background . A number of studies have revealed that inflammation-based prognostic scores, such as Glasgow prognostic score (GPS), modified Glasgow prognostic score (mGPS), and C-reactive protein and albumin ratio (C/A ratio), are associated with poor outcome in cancer patients. However, until now, no study has investigated the role of these prognostic scores in a cohort of neoadjuvant-treated esophageal adenocarcinomas (nEAC) and squamous cell carcinomas (nESCC). Methods . Patients had laboratory measurements within three days before resection. GPS, mGPS, and C/A ratio were tested together with established clinicopathological factors in simple and multiple Cox regression analysis of overall survival (OS) and disease-free survival (DFS). Results . A total of 283 patients (201 EAC and 82 ESCC) with locally advanced esophageal cancer were enrolled. 167 patients received neoadjuvant treatment (59.0%). Simple analysis revealed that there were significant differences in cancer-specific survival in relation to elevated C-reactive protein (p = 0.011 ), lymph node status (p < 0.001 ), UICC stage (p < 0.001 ), and nEAC (p = 0.005 ). mGPS (p = 0.024 ) showed statistical significance in simple analysis. No statistical significance could be found for GPS (p = 0.29 ), mGPS (p = 0.16 ), and C/A ratio (p = 0.76 ) in multiple analysis. Conclusion . The investigated prognostic scores should be used and interpreted carefully, and established factors like histology, including tumor size and differentiation, lymph node involvement, and status of resection margin remain the only reliable prognostic factors for patients suffering from resectable EC.